Growing up tough: Comparing the effects of food toughness on juvenile feeding in Sapajus libidinosus and Trachypithecus phayrei crepusculus. Issue 98 (September 2016) - Chalk-Wilayto, Janine; Ossi-Lupo, Kerry; Raguet-Schofield, Melissa
Abstract: Studies of primate feeding ontogeny provide equivocal support for reduced juvenile proficiency. When immatures exhibit decreased feeding competency, these differences are attributed to a spectrum of experience- and strength-related constraints and are often linked to qualitative assessments of food difficulty. However, few have investigated age-related differences in feeding ability relative to mechanical property variation across the diet, both within and among food types. In this study, we combined dietary toughness and feeding behavior data collected in the wild from cross-sectional samples of two primate taxa, Sapajus libidinosus and Trachypithecus phayrei crepusculus, to test the prediction that small-bodied juveniles are less efficient at processing tough foods than adults. We defined feeding efficiency as the time spent to ingest and masticate one food item (item bout length) and quantified the toughness and size of foods processed during those feeding bouts. To make the datasets comparable, we limited the dataset to foods processed by more than one age class and opened without tools. The overall toughness of foods processed by both species overlapped considerably, and juveniles and adults in both taxa processed foods of comparable toughness. Feeding efficiency decreased in response to increasing food toughness in leaf monkeys and in response to food size in both taxa. Age was found to be a significant predictor of bout length in leaf monkeys, but not in bearded capuchins. Juvenile S. libidinosus processed smaller fruits than adults, suggesting they employ behavioral strategies to mitigate the effect of consuming large (and occasionally large and tough) foods. We suggest future intra- and interspecific research of juvenile feeding competency utilize intake rates scaled by food size and geometry, as well as by detailed measures of feeding time (e.g., ingestion vs. mastication), in addition to food mechanical properties to facilitate comparisons across diverse food types and feeding behaviors.